PEMBERDAYAAN UKM SUWARDI SEBAGAI UPAYA MENINGKATKAN NILAI JUAL DAN PRODUKTIVITAS KERUPUK AMPAS TAHU - Al Hakim, Reza Azizul Nasa; Akbar, Mohammad Irham; Gumintang, Bagas (Universitas Mataram, 2025)
Kalisari Village, Cilongok District, Banyumas Regency, is known as a tofu production center that generates a large amount of tofu dregs waste. This waste has been underutilized and often causes environmental problems, as its use has generally been limited to animal feed. UKM Suwardi emerged with an innovation to process tofu dregs into crackers with economic value, yet still faces challenges in digital marketing, simple packaging design, and a production process highly dependent on weather conditions. This community service program aims to enhance the market value, productivity, and competitiveness of tofu dregs crackers through the application of appropriate technology and strengthened marketing strategies. The implementation methods included socialization, training on digital marketing and packaging design, the provision of a drying oven and food sealer, intensive mentoring, and continuous evaluation. The results show an increase in production capacity from 50 kg to 75 kg per day, improved product hygiene due to a closed drying process independent of sunlight, and more attractive and informative packaging. In addition, the owner and workers gained new skills in utilizing social media and online marketplaces for promotion, expanding the market reach from local distribution to digital platforms. This program also improved consumer trust, as reflected in an increase in new customers and higher sales turnover. Therefore, this community service activity successfully addressed the partner’s problems by improving productivity, product quality, and marketing strategies of UKM Suwardi.